(untitled) (The Review of Diabetic Studies, 2024)
Introduction: Diabetes has become a major public health concern in Malaysia, and its prevalence keeps increasing every year. Improper knowledge of diabetes could lead to uncontrolled diabetes management and further complications from diabetes such as retinopathy, nephropathy, and neuropathy. Therefore, an educational intervention study was conducted to evaluate the effectiveness of educational intervention in improving the knowledge, attitude, perception, and practice of diabetic patients towards diabetes. Patients-Methods: A total of 82 diabetic patients were randomly divided into control and intervention groups, and the data was collected using a structured questionnaire. Results: The results showed that the diabetic patients’ knowledge, attitude, perception, and practice were significantly associated with their age and type of diabetes. The respondents’ knowledge of diabetes and its complications significantly improved after a month of intervention, from 82.93% and 70.73% at baseline to 97.22% and 100% after intervention for foot problems and eye diseases, respectively. Conclusion: This study concluded that the effective implementation of educational interventions has improved the knowledge, attitude, perception, and practice of diabetic patients towards diabetes. Further, awareness about a healthy diet and foot examination is needed to prevent future complications related to diabetes.